Maternal hemoglobin change from early pregnancy to second trimester is associated with risk of gestational diabetes mellitus: a retrospective cohort study - Sulhariza, Husni Zain; Zalilah, Mohd Shariff; Geeta, Appannah (Frontiers in Nutrition, 2023)
The accrual of iron that is reflected in high maternal hemoglobin (Hb) status is increasingly recognized as a risk factor for gestational diabetes mellitus (GDM). Changes in maternal Hb level could also implicate glycemic status in pregnancy. This study aimed to determine the associations between maternal Hb levels and their changes with GDM. A total of 1315 antenatal records of mothers with singleton pregnancies from eight health clinics of a district in the northern region of Peninsular Malaysia who delivered between 1st January 2016 - 31st December 2017 were analyzed retrospectively. Socio-demographic, anthropometric, obstetrical, and clinical data were extracted from the records. Hb level data were extracted at two-time points: booking (<14 weeks) and second trimester (14 – 28 weeks). Change in Hb was determined by subtracting the Hb level in the second trimester from the booking Hb level and was categorized as decreased, unchanged, and increased Hb. The associations between maternal Hb levels and their changes with GDM risk were analyzed using multiple regression, adjusting for covariates in four different models. Model 1: maternal age and height. Model 2: covariates of Model 1 added with parity, history of GDM, and family history of diabetes. Model 3: covariates of Model 2 added with iron supplementation at booking. Model 4: covariates of Model 3 added with Hb level at booking. Unchanged Hb level from booking to second trimester was significantly associated with GDM risk in Model 1 (AOR: 2.55; 95% CI: 1.20, 5.44; p<0.05), Model 2 (AOR: 2.45, 95% CI: 1.13, 5.34; p<0.05) Model 3 (AOR: 2.42; 95% CI: 1.11, 5.27; p<0.05), and Model 4 (AOR: 2.51; 95% CI: 1.15, 5.49; p<0.05). No significant associations were observed between maternal Hb levels and GDM in the study. Unchanged Hb levels from the booking (<14 weeks of gestation) to the second trimester (14 – 28 weeks) increased GDM risk. Further investigation is warranted to evaluate the associations between changes in maternal Hb and GDM risk and to identify potential factors influencing this relationship.